Pengaruh Budaya Hukum Terhadap Pembangunan Hukum Di Indonesia (Kritik Terhadap Lemahnya Budaya Hukum di Indonesia) - Any Ismayawati (PRANATA HUKUM, 2011)
The developmental of legal culture of Indonesia experienced a shift away fromnature, personality and identity of the Indonesian nation,.Legal cultural development of Indonesia at this time was very down. Shifting of the Indonesian legal culture is influenced by internal and external factors. Internal factors related to the morals understanding of Indonesia, while the external factors associated with the development of technologies and ideas or thoughts from a foreign culture. The condition of the legal culture is one factor that resulted in his chaos of law in Indonesia because the legal culture is one of the most influential law component, both in the establishment of law and in law enforcement. The establishment of law and law enforcement is a form of legal development, it can be said with the collapsed culture of law it will have a negative impact on the development of the law.